Communication and trafficking in persons in contexts of war. Case study of the conflict in Ukraine - Parra Ferreras, Sara (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2023)
Human trafficking has become a global problem, constituting one of the most lucrative criminal businesses in the world according to the International Labor Organization. Among the factors that increase the risk of human trafficking, war is one of the causes that generate an increase in the number of victims. This text focuses on the conflict present in Ukraine, analysed from the point of view of communication, with the media coverage that has been given by the media with an online presence in Spanish, understanding the information as a tool against this scourge.